Estimate the Efficiency of Agricultural Investment in Egypt - Hala Ali; Dina Ewis (New Valley Journal of Agricultural Science, 2022)
The research aims to estimate the Efficiency of investments directed to the agricultural sector by analyzing the current situation of national and agricultural investment in Egypt (2006/2005 - 2020/2021) and measuring the investments made in Egypt over the study period. In order To achieve the objectives of the research, the most important criteria that reflect the efficiency of agricultural investment were estimated, as well as the use of descriptive and quantitative analysis methods to estimate simple and multiple regression relationships in the double logarithmic form of the research data issued various institutions and government agencies. The study's findings revealed that, on average, the public sector's return on investment was higher than 1, reached about 61,116 million UDS, whereas the private sector's was lower, at about 0.032 million USD, demonstrating the inefficiency of public sector investments in comparison to investments. In the agriculture sector, the private sector has grown along with the investment multiplier in both the public and private sectors .As for the coefficient of settlement, it was shown that the efficiency of agricultural investment directed to the public and private sector was weak, as it was shown by estimating the agricultural capital intensification coefficient, the intensity of the use of the human factor in the agricultural sector by a percentage greater than The percentage increase in investments directed to this sector.